Can you estimate body composition in dogs from photographs?. Issue 1 (December 2016) - Gant, Poppy; Holden, Shelley; Biourge, Vincent; German, Alexander
Abstract Background A validated method for assessing the visual characteristics of body condition from photographs (vBCS), would be a useful initial screening tool for client-owned dogs. Methods In this retrospective study, photographs taken before and after weight loss from 155 overweight and obese dogs attending a weight management referral clinic were used in designing and testing the feasibility of vBCS. Observers with a range of experience examined the photographs, and estimated body condition indirectly (vBCS) using three different methods. In the first method (vBCSmeasured ), the ratio of abdominal width to thoracic width (A:T) was measured, and cut-points used to determine body condition; the second method (iBCSsubjective ) involved semi-quantitative examination using visual descriptors of BCS; the third (vBCSadjusted ) was a combined approach whereby A:T ratio was first determined, and the final score modified if necessary after assessing photographs. Results When an experienced observer performed vBCS, there were moderate-to-good associations between body fat (measured by dual-energy X-ray absorptiometry) and the three vBCS methods (median Rs : 0.51-0.75;P < 0.001), and also moderate-to-substantial agreement with actual BCS (median kappa 0.51–0.63;P < 0.001). For operators with a range of experience, moderate-to-substantial agreement was generally seen between actual BCS and the scores determined by all three methods (median Kappa 0.55–0.70, P < 0.001), but the strength of agreement varied amongst observers. Age, sex, breed, coat length, and coat colour had no significant effect on vBCS (P > 0.05 for all). Compared with ideal weight and obese dogs, errors in assessing body condition were more common for overweight dogs (e.g. BCS 6–7/9, P < 0.001) by vBCSadjusted (P = 0.008), and vBCSsubjective (P = 0.021), but not by vBCSmeasured (P = 0.150). For vBCSadjusted, body condition was most often overestimated whilst, for vBCSsubjective, body condition was most often under-estimated. Conclusions An estimate of body condition can be obtained from an indirect assessment of photographs, but performance varies amongst observers.